Identification of Sport Talent Scouting for New Students of Physical Education Study Program - Puspodari, Puspodari; Lusianti, Septiyaning; Himawanto, Wasis; Irianto, Sony (CV. Nusantara Sporta, 2024)
Sport is an activity that moves the body for various purposes, such as hobbies, losing weight, and achieving achievements. However, national sporting achievements still lag behind Asian countries such as China, Japan, Korea, Thailand and Vietnam, which are now a big threat at the SEA Games. This lag shows the need to improve the national sports development system, including the development of talented athletes. In the modern era, the selection of talented athletes is carried out using relevant test methods, such as the Australian Sport Search. This method helps identify talent based on anthropometric aspects and physical abilities, making it easier to determine potential and interest in sports from an early age. Talent development is the process of discovering individual potential, such as intelligence, skills and innate traits, to analyze opportunities in certain sports. With proper coaching, talented individuals can be developed into potential athletes who are able to reach peak achievements, supporting the progress of national sports.